Gay guerrilla: Julius Eastman and his music - Levine Packer, Renée 1940-; Leach, Mary Jane (Rochester University of Rochester Press, 2015)
Composer-performer Julius Eastman (1940-90) was an enigma, both comfortable and uncomfortable in the many worlds he inhabited: black, white, gay, straight, classical music, disco, academia, and downtown New York. His music, insistent and straightforward, resists labels and seethes with a tension that resonates with musicians, scholars, and audiences today. Eastman's provocative titles, including Gay Guerrilla, Evil Nigger, Crazy Nigger, and others, assault us with his obsessions. Eastman tested limits with his political aggressiveness, as reflected in legendary scandals like his June 1975 performance of John Cage's Song Books, which featured homoerotic interjections, and the uproar over his titles at Northwestern University. These episodes are examples of Eastman's persistence in pushing the limits of the acceptable in the highly charged arenas of sexual and civil rights. In addition to analyses of Eastman's music, the essays in Gay Guerrilla provide background on his remarkable life history and the era's social landscape. The book presents an authentic portrait of a notable American artist that is compelling reading for the general reader as well as scholars interested in twentieth-century American music, American studies, gay rights, and civil rights.BR Contributors: David Borden, Luciano Chessa, Ryan Dohoney, Kyle Gann, Andrew Hanson-Dvoracek, R. Nemo Hill, Mary Jane Leach, Renee Levine Packer, George E. Lewis, Matthew Mendez, John Patrick Thomas Renee Levine Packer's book This Life of Sounds: Evenings for New Music in Buffalo received an ASCAP Deems Taylor Award for excellence. Mary Jane Leach is a composer and freelance writer, currently writing music and theatre criticism for the Albany Times-Union.